(untitled) (Revista Lusófona de Educação, 2025)
School Nursing plays an important role in Professional and Technological Education (EPT) by contributing to citizen education. However, it faces challenges in terms of recognition and integration. In order to turn the school into an environment conducive to health promotion and consolidate an approach aligned with the principles of EPT, it is essential to understand conceptions, perceptions and meanings elaborated by the community about nursing. Therefore, this study analysed social representations constructed by the school community about the work of nursing professionals in the EPT, based on Moscovici’s Theory of Social Representations. The study was carried out with students, teachers, technicians and managers at IFMA, using focus groups and thematic analysis. Representations related to the welcoming profile, the educational role and the biomedical model were identified, as well as challenges such as devaluation, overload and uncertainty about the scope of work. The conclusion is that nursing in the EPT needs to be better defined and understood by the community in order to act in a transformative way according to the conceptions of integral human formation. Keywords: Social Representations; School Nursing Services; Professional Education